PENINGKATAN KEMAMPUAN MEMBACA BERSUARA SISWA KELAS IV SD NEGERI 02 PANINGGAHAN MELALUI TEKNIK PEMODELAN FONOLOGIS - Mimi Sri Irfadila; Atmazaki .; Jufrizal . (Fakultas Bahasa dan Seni UNP, 2013)
Abtract: Learningthe Indonesian Language, specially reading aloudin Elementary School must use varioustechniques. This causes,less motivatedstudentstolearn independently and less ability in reading aloud. The solutiontoresolveproblems is apply ofmodeling phonologicaltechniques in teachingreading aloud.This technique aims at improvingreading skills. The phonologicalmodeling technique can beappliedby focusing onthepronunciationof phonemes. This research isa classroom action researchusingdescriptivemethods. The population are all of student at SDN 02 Paninggahan. The sample is fourthgrade studentsof SDN02Paninggahan.The concluded of the research are:1)learnersare more motivatedto participate inlearningIndonesian language withphonologicalmodelingtechniques. 2)Increasedthoroughnesseveryaspect/indicatoron the first cycleandsecond cycleincreased.The increaseoccurred inthe pronunciation ofthe phoneme/f/, /u/, /a/, /i/, /k/, and /n/. Kata kunci: kemampuan membaca bersuara, teknik pemodelan fonologis